Hamburger‐liked selenium doped‐zinc oxide decorated in graphene for assessing enhanced phenolic compound removal. Issue 6 (21st September 2022) - Trinh, Dinh Ngoc; Huong, Le Minh; Hai, Nguyen Duy; Thinh, Doan Ba; Dat, Nguyen Minh; Ky, Nham Minh; Phuc, Bui Ngoc; Phuc, Nguyen Thien; Khoa, Ta Dang; Oanh, Doan Thi Yen; Phong, Mai Thanh; Hieu, Nguyen Huu
Abstract: Herein, selenium doped‐zinc oxide decorated in graphene (Se@ZnO/Gr ‐ SZG) was facilely synthesized via the hydrothermal method with orange peel extract as a reducing agent. The composite was well characterized by various modern analytical methods. In terms of the characterization analysis, the synthesized Se@ZnO with high crystallinity has a hamburger‐like structure uniformly distributed on the graphene sheets. The effects of catalyst dosage, H2 O2 volume, and pH on the photodegradation of para‐nitrophenol are studied. Besides, the investigation of the photodegradation performance revealed a 99.22 % elimination under treatment of 15 mg of SZG catalyst in the presence of 1.25 mL H2 O2 at pH 9 for 100 min UV irradiation. Accordingly, the results express the potentiality of the material in organic matter treatment. Abstract :